The Rise of Digital Health: A Bibliometric Review of Social Media and Online Platforms for STI Education in Adolescents - Henky Yoga Prasetya; Sri Ratna Rahayu; Widya Hary Cahyati (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Sexually Transmitted Infections (STIs) continue to increase, especially among adolescents. Minimal sexual education and risky behaviors are the main factors in STIs. In the digital era, social media has the potential to be an effective means of STI education for adolescents. However, scientific studies related to this matter are still limited. This study aims to map the current research landscape regarding the use of social media and online platforms for STI education among adolescents. Materials and methods: This study uses a bibliometric approach. Literature searches were conducted in the Scopus database using keywords such as